Outcomes of Mechanical Engineering Education in Specialized Projects With Respect to Entry Level Practice - Paudel, Guna Raj (Journal of the Institute of Engineering, 2009)
The study measured the extent of importance, desired and existing level of competences of seven proposed outcome statements related to specialized project works in Bachelor's Degree in Mechanical Engineering. A structured questionnaire was distributed to three groups of respondents namely employers, graduates, and teachers associated to mechanical engineering. Collected data were analyzed with the help of SPSS technology. The findings showed that all seven outcome statements were very important in the profession indicating the need of the fulfilment of higher level of competencies in these areas by engineering education. On the opposite the study showed significant differences between the mean values of desired and existing level of competences indicating the desire of additional efforts to improve the quality of engineering education. Key words: Mechanical Engineering; education Journal of the Institute of Engineering, Vol. 7, No. 1, July, 2009 pp. 127-134 doi: 10.3126/jie.v7i1.2071